(3bUjOI YbGFO SYOj Hf JGLs - (3SYOj Hf JGLs
(3ChdgG (B:s
(3HSe Gddg JhcdfG HUOb cd MGd Ydi Gddg GdebOQ Pj GdLdGd (B** (3gh GdYdGe ddCSQGQ cdG hNdGb GdNdGFb Ph GdJYGdj (B** (3gh Gddg GdYdj HdG YOjd gh GdMb GdYRjR HdG eKGd s
(3BNQgG (B:s
(3ajSQ CeQfG aj OGQ OfjG haj GdYbHi Cfdfj HGdefGd aUd Ydi QShdc gGTej bQjTj fHj Pj Gd (B** (3hUd Ydi UMGHJg hBdg ge NjQ GdUMGH hNjQ Bd s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds